Reducing risk of head injury in youth soccer: An extension of behavioral skills training for heading. Issue 1 (29th March 2019) - Quintero, Laura M.; Moore, James W.; Yeager, M. Garrett; Rowsey, Kyle; Olmi, D. Joe; Britton‐Slater, Joshua; Harper, Michaela L.; Zezenski, Lauren E.
Abstract : Recently, concerns regarding sport‐related concussions have increased within the research literature, the media, and popular culture. One potential source of soccer‐related concussions involves the purposeful striking of the ball with one's head (i.e., heading). There is currently limited research on an effective teaching method to improve safe heading technique. In the current study, Behavior Skills Training (BST) was evaluated as a method to teach correct heading techniques to youth soccer players. BST increased the percentage of correct steps for each player based on a task analysis of heading. Based on social validity questionnaires administered to players and the coach, BST was rated as an acceptable form of training. After the final training session, experienced coaches rated each player as having improved from baseline to training.